Association between neck circumference and lipid profile: a systematic review and meta-analysis of observational studies. (15th January 2021) - Shokri-Mashhadi, Nafiseh; Moradi, Sajjad; Mohammadi, Hamed; Ghavami, Abed; Rouhani, Mohammad Hossein
Abstract: Aims: Previous studies suggested that neck circumference (NC) as a new, simple, and valuable tool for the measuring obesity. However, the results of studies regarding the relationship between blood lipids and neck circumference were inconsistent. Therefore, we aimed to perform a systematic review and meta-analysis to summarize the association between NC and lipid profiles in adults. Methods and results: PubMed and Scopus electronic databases were searched until 30 June 2018 to find articles that reported the association between NC and blood lipids. Mean serum lipids and variables contributed to heterogeneity were extracted. Sources of inter-study heterogeneity were determined by subgroup analysis. Of 2490 publications identified, 33 studies were included in the qualitative and quantitative synthesis. We found an inverse correlation between NC and high-density lipoprotein cholesterol [HDL-C; overall Fisher's Z  = −0.18; 95% confidence interval (CI): −0.21, −0.15]. Furthermore, we found positive associations between NC and total cholesterol (TC; overall Fisher's Z  = 0.11; 95% CI = 0.06, 0.16), low-density lipoprotein cholesterol (LDL-C; overall Fisher's Z  = 0.1; 95% CI = −0.04, 0.16), and triglyceride (TG; overall Fisher's Z  = 0.21; 95% CI = 0.17, 0.25) in men. Neck circumference was directly correlated to TC (overall Fisher's Z  = 0.1; 95% CI = 0.01, 0.19) and LDL-C (overall Fisher's Z  = 0.16; 95% CI = 0.12, 0.20) in healthy and unhealthy women, respectively. There was no correlation between NC and serum concentration of TC (overall Fisher's Z  = 0.01; 95% CI = −0.02, 0.03) and LDL-C (overall Fisher's Z  = 0.09; 95% CI = 0.02, 0.16) in unhealthy and healthy women, respectively. Conclusion: Higher NC in unhealthy men was strongly indirectly associated with HDL-C, and directly related to LDL-C, TG, and TC. In unhealthy women, higher NC was inversely associated with HDL and directly related to LDL-C.